HYDROLOGICAL WATER BALANCE PROJECTION AT MAJOR RESERVOIR CATCHMENTS IN INDONESIA : RIAM KANAN, SAGULING, BILI-BILI, BATU TEGI - Rachmawati, Sartika
Climate change is a problem that has an impact on several aspect in life. According to data from Badan Meteorologi dan Geofisika (BMKG), Indonesia experienced changes in annual rainfall in the 1991-2010 period compared to the 1971-1990 period. Some areas of Sulawesi and several points in Bengkulu and South Kalimantan experienced an increase in rainfall reaching 120 mm. There are also areas that experienced decreasing, in all of Papua Island and the highest point of decline in several areas of Central Kalimantan. This condition certainly indicates a climate change will affect the availability of water around the location. In this study, an analysis was conducted to determine the trend of the hydrological water balance that might occur due to the influence of climate change. The selection of the study location is the catchment area of the reservoir which has a large change in annual rainfall and the size of the reservoir and the benefits to the community. The analysis was carried out only by considering hydrometeorological parameters, rainfall and evapotranspiration. The projection data uses the CORDEX RCP 8.5 (2020-2045) and observational climate data by BMKG station (1999-2005) as a model data corrector also as training data to be projected using the ARIMA method and linear regression. The results of the analysis show that the evapotranspiration value of the four catchment areas of the reservoir have a positive trend, with the highest increase in the Bili-bili catchment area in Maros reaching 4% in the rainy season and 3% in the dry season. This is influenced by the amount of sunshine duration above 10 hours. In contrast to evapotranspiration, the value of effective rainfall that occurs in the four catchment has a negative trend throughout the catchment although it is not very significant. During the dry season, all location predicted there will be no runoff and no infiltration.